2024
DOI: 10.1021/jacs.3c11225
|View full text |Cite
|
Sign up to set email alerts
|

A General Platform for Visible Light Sulfonylation Reactions Enabled by Catalytic Triarylamine EDA Complexes

Juan D. Lasso,
Durbis J. Castillo-Pazos,
Jan Michael Salgado
et al.

Abstract: Catalytic electron donor–acceptor (EDA) complexes have recently emerged as a powerful and sustainable alternative to iridium- and ruthenium-based photoredox synthetic methods. Yet, these complexes remain underexplored and reliant on the use of meticulously designed acceptors that require previous installation. Herein, we report a novel EDA complex employing tris(4-methoxyphenyl) amine as a catalytic donor for the sulfonylation of alkenes using inexpensive and readily available sulfonyl chlorides. Applying this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Combining the results from mechanistic studies and previously reported investigations together, we propose the following mechanism (Figure ). Initially, sodium 4-methylphenylsulfinate 2a combines with 4-methyl- N -(2-(phenylethynyl)­phenyl)­benzenesulfonamide 1a to form an EDA complex I in the presence of K 2 CO 3 . , Upon light irradiation, the generated EDA complex I undergoes a SET from the donor to the acceptor, , forming an oxygen-centered radical II-1 resonating with sulfonyl radical II-2 and an N -sulfonamide radical anion III .…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Combining the results from mechanistic studies and previously reported investigations together, we propose the following mechanism (Figure ). Initially, sodium 4-methylphenylsulfinate 2a combines with 4-methyl- N -(2-(phenylethynyl)­phenyl)­benzenesulfonamide 1a to form an EDA complex I in the presence of K 2 CO 3 . , Upon light irradiation, the generated EDA complex I undergoes a SET from the donor to the acceptor, , forming an oxygen-centered radical II-1 resonating with sulfonyl radical II-2 and an N -sulfonamide radical anion III .…”
supporting
confidence: 64%
“…Alternative, sulfonation via radical involved cascade cyclization processes has been developed, which is initiated by oxidation of a sulfinate anion through photoredox catalysts or excess peroxides . Despite these achievements, there is still a pressing need for general photocatalyst- and transition-metal-free strategies that enable the facile preparation of sulfone-containing indoles …”
mentioning
confidence: 99%
“…Recently, a variety of commonly accessible and efficient sulfonation reagents including sodium sulfite, sulfinic acid, sulfonyl chloride, and sulfonyl hydrazine have been widely studied and applied in different methodologies . Sulfuryl chloride could be reacted with numerous compounds containing unsaturated bonds due to its easy availability and high reactivity . Inspired by the references above and our interest in constructing indolines, we hypothesized whether C3-substituted indolines could be constructed using a new skeleton with sulfuryl chlorides in one-step via the 1,5-HAT process.…”
Section: Introductionmentioning
confidence: 99%